2001
DOI: 10.1093/rheumatology/40.6.645
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Internet‐based rheumatology education (http://rheuma.bham.ac.uk)

Abstract: These data indicate that it is possible to use the Internet to deliver medical information to its target audience, and that this process can have some impact on the way disease is self-managed. This information may aid more focused website design to maximize the use and potential benefits of such a resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
15
0
3
Order By: Relevance
“…Diese Situation muss als Chance zur Vertrauensbildung zwischen Arzt und Patient, zur Zusammenarbeit und Unterstützung des Patienten in der aktuellen Behandlung sowie der Bereitstellung der "up to date"-Information zu spezifischen, ggf. seltenen Erkrankungen genutzt werden [8,12,28,36,43]. Das Internet ist zu einem wichtigen Medium geworden, um Patienten in der Entwicklung zu emanzipierten Verbrauchern zu unterstützen und das Selfmanagement der Patienten zu verbessern [27,43].…”
Section: Computer-und Internetzugangunclassified
See 1 more Smart Citation
“…Diese Situation muss als Chance zur Vertrauensbildung zwischen Arzt und Patient, zur Zusammenarbeit und Unterstützung des Patienten in der aktuellen Behandlung sowie der Bereitstellung der "up to date"-Information zu spezifischen, ggf. seltenen Erkrankungen genutzt werden [8,12,28,36,43]. Das Internet ist zu einem wichtigen Medium geworden, um Patienten in der Entwicklung zu emanzipierten Verbrauchern zu unterstützen und das Selfmanagement der Patienten zu verbessern [27,43].…”
Section: Computer-und Internetzugangunclassified
“…seltenen Erkrankungen genutzt werden [8,12,28,36,43]. Das Internet ist zu einem wichtigen Medium geworden, um Patienten in der Entwicklung zu emanzipierten Verbrauchern zu unterstützen und das Selfmanagement der Patienten zu verbessern [27,43]. Die Ziele eines möglichen internetgestützten, modernen "Disease Management" bestehen darin, eine Verbesserung der Arzt-Patientenbeziehung, der Patientenaufklärung und des Monitoring und damit auch des Outcome sowie eine allgemeine Kostenreduktion zu erzielen [11].…”
Section: Computer-und Internetzugangunclassified
“…Based on this pilot study a short computer-based questionnair e was produced and published on our previously establishe d ArthritisHelp patient information website. 4 In order to increase awareness of this questionnaire , a post was put up on a popular US-based forum, links were requested at numerous sites and efforts were made to register the site with a wide range of search engines. A total of 510 completed questionnaire s were acquired during the period of study.…”
Section: Interviews and Questionnaire Smentioning
confidence: 99%
“…However, there has been some concern about 'dumbing-down' reducing the value of educational material 8 and certainly, our survey of patient information needs and a review of the comments section of our general arthritis patient website (www.rheumatology.bham. ac.uk = primer.html) 4 suggested that many patients found that much of the information previously available was too basic for their needs and that a greater variety of information was needed. An editorial team that included both nursing and clinical staff checked the content and a total of 50 online pages were produced.…”
Section: Website Constructionmentioning
confidence: 99%
“…Es konnte gezeigt werden, dass das "Selfmanagement" der Patienten, u.a. unterstützt durch die Nutzung des Mediums Internet, eine entscheidende Rolle in Bezug auf die Arzt-Patienten-Beziehung, die Patientenaufklärung, die Verlaufskontrolle der Erkrankung und damit die Prognose spielt [8][9][10]. Eine Reihe von epidemiologischen Studien aus westlichen Ländern, aber auch aus ressourcenarmen Entwicklungsländern, konnte die Effizienz von Patientenfragebogen für die Früherkennung entzündlich-rheumatischer Erkrankungen aufzeigen [11][12][13][14][15][16][17][18].…”
Section: Introductionunclassified